Railway dreaming: Lessons for economic regulators from Aboriginal resource management lore - Wills-Johnson, Nick (Planning and Transport Research Centre, 2008)
A third party access regime is intended to open railway track for use by those other than its owner. In so doing, policymakers hope that the monopoly a vertically integrated railway company has over rail transport region will be broken, and that above-rail operators will compete for business, using the railway track to do so on fair and reasonable terms of access that are overseen by a regulator.However, an access regime does more than create competition; it also changes the property rights associated with the railway track, transferring some from the original owner to the access seekers who now also operate their trains upon the track. This means the nature of the asset changes; it is no longer purely private property, but is in fact a form of common property resource (CPR). If the track and its access regimes are to remain sustainable into the longer term, the CPR nature of the track must be reflected in its governance. Otherwise, Hardin's (1968) 'tragedy of the commons' may ensue. This paper focuses on CPR governance mechanisms, and in particular on those used by Aboriginal Australians in the management of their most common resource; the land. Whilst on the surface, there might be few obvious links between a hunter-gatherer society and a railway, in fact the principles used by Aboriginal Australians are quite fundamental, and could usefully support competition and third party access.